Digital Risk Manajement: Tantangan dan Solusi di Era Transformasi Digital Organisasi Pendidikan - Nasyanda Indah Joelia; Irsyad, Irsyad; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2025)
Digital transformation in Indonesia’s education sector has accelerated through the use of LMS platforms, online administration, and large-scale data integration, yet this progress is not matched by adequate digital risk management, increasing vulnerability to cyber threats. Based on a literature review, this study identifies that digital risks arise from technical weaknesses such as poor encryption, lack of intrusion detection, and weak data protection as well as non-technical issues including low security literacy, infrastructure gaps, and weak institutional governance, with human error as the dominant cause of incidents. The study emphasizes the need for stronger security policies, improved digital competencies, standardized security technologies, and the adoption of frameworks like ISO 31000 and the NIST Cybersecurity Framework. Ultimately, digital resilience in education requires synergy between effective policies, structured IT governance, and sustainable technological infrastructure.